Hodgkin's Lymphoma In Low-Income Countries: Experience Of Togo - Padaro, Essohana; M C Womey, Kodzovi; Layibo, Yao; R Adandodo, Kadara; Magnang, Hèzouwè; D I Kueviakoe, Mensah (Journal of Hematology and Oncology Research, 2024)
While highly curable in developed countries, Hodgkin's lymphoma (HL), remains a significant challenge for resource-limited ones. This study aimed to describe the profile of HL in Togo. This was a retrospective, descriptive study conducted at the Clinical Hematology Department of the Campus University Hospital Center in Lomé, Togo. It focused on patient records diagnosed with HL between January 1, 2006, and December 31, 2022. Various variables such as age, gender, histological type of HL, Ann Arbor stage, prognostic classification, therapeutic protocol used, and patient outcomes were examined. The annual incidence of HL was 1.5 with a mean age of 38.7 years (range 12-63). Lymph node enlargement was the primary clinical sign (100%). Histologically, classical HL was found in 21 patients (87.5%). Staging was conducted for 16 (66.7%) patients, among whom 11 (66.7%) were at an advanced stage, and 6 (37.5%) had an unfavorable prognosis. The ABVD protocol was used in 13 patients (54.2%), receiving between 1 and 6 cycles. One patient achieved complete remission (4.1%), three deceased (12.5%), and 17 (71%) were lost to follow-up. Hodgkin's lymphoma prognosis remains unfavorable with low remission rates in Togo. Improving the technical facilities will ensure better management of this lymphoma.
Keywords: Hodgkin's lymphoma; epidemiology; Togo